Analisis implementasi sistem informasi manajemen rumah sakit pada unit rekam medis - Pratiwi, Era (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The Hospital Management Information System (SIMRS) is a crucial tool for improving service quality, operational efficiency, and data recording accuracy in hospitals, including in the medical records unit. Syekh Yusuf Regional General Hospital, Gowa, has implemented SIMRS since 2018, but is still in the transition phase from a manual to a digital (hybrid) system. This situation requires an evaluation of the system's implementation to ensure its effectiveness and sustainability. Purpose: To analyze the implementation of SIMRS in the medical records unit based on human, organizational, and technological aspects (the HOT-Fit model). Method: This study used a qualitative phenomenological approach with four informants (the head of medical records, two medical records officers, and one IT officer). Data were collected through in-depth interviews, observation, and documentation, then analyzed through the stages of reduction, presentation, and conclusion drawing. Results: SIMRS implementation went quite well. The human resource aspect showed that most staff understood how to use the system, although technical guidance was still needed. The organizational aspect demonstrated management support in the form of regular training and supervision. Furthermore, the technological aspect assessed the system as adequate but was hampered by internet network and device specifications. Conclusion: SIMRS implementation has shown positive progress, but optimization is still needed through infrastructure improvements, user competency, and ongoing managerial support. Keywords: Hospital Information System; Implementation; Medical Records; SIMRS. Pendahuluan: Sistem Informasi Manajemen Rumah Sakit (SIMRS) merupakan alat penting dalam meningkatkan mutu pelayanan, efisiensi operasional, dan akurasi pencatatan data di rumah sakit, termasuk pada unit kerja rekam medis. RSUD Syekh Yusuf Gowa telah menerapkan SIMRS sejak 2018, namun masih berada pada tahap transisi dari sistem manual ke digital (hybrid). Kondisi ini menuntut adanya evaluasi terhadap implementasi sistem untuk memastikan efektivitas dan keberlanjutannya. Tujuan: Menganalisis implementasi SIMRS pada unit kerja rekam medis berdasarkan aspek manusia, organisasi, dan teknologi (model HOT-Fit). Metode: Penelitian ini menggunakan pendekatan kualitatif fenomenologi dengan empat informan (kepala rekam medis, dua petugas rekam medis, dan satu petugas IT). Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil: Implementasi SIMRS berjalan cukup baik. Aspek manusia menunjukkan sebagian besar petugas memahami penggunaan sistem meskipun masih memerlukan bimbingan teknis. Aspek organisasi menunjukkan dukungan manajemen berupa pelatihan dan supervisi rutin. Selanjutnya aspek teknologi, sistem dinilai memadai namun terkendala jaringan internet dan spesifikasi perangkat. Simpulan: Implementasi SIMRS menunjukkan perkembangan positif, namun optimalisasi masih dibutuhkan melalui peningkatan infrastruktur, kompetensi pengguna, dan dukungan manajerial berkelanjutan. Kata Kunci: HOT-Fit; Implementasi; Rekam Medis; SIMRS.